Doxycycline inhibits the progression of metastases in early-stage osteosarcoma by downregulating the expression of MMPs, VEGF and ezrin at primary sites. (2022) - Hadjimichael, Argyris C.; Foukas, Athanasios F.; Papadimitriou, Evangelia; Kaspiris, Angelos; Peristiani, Chrysostomi; Chaniotakis, Ioannis; Kotsari, Maria; Pergaris, Alexandros; Theocharis, Stamatios; Sarantis, Panagiotis; Christopoulou, Magdalini; Psyrri, Amanda; et al.
Highlights: Doxycycline exhibits anti-cancer properties against osteosarcoma in vitro and in vivo replicated clinical scenarios . Doxycycline prevents the progress of pulmonary micro - metastases to macro - metastases at early-stage osteosarcoma. The expression of the angiogenetic markers MMPs, VEGFA and ezrin is downregulated by doxycycline in primary osteosarcoma. Doxycycline enhances the anti - tumour activity of macrophages in pulmonary metastases. Abstract: Introduction: Osteosarcoma (OS) is the most common primary osseous malignant tumour, with high propensity to metastasise in lungs. Pulmonary micro-metastases are present in up to 80% of patients at initial diagnosis and they are associated with significantly worse prognosis. Doxycycline (Dox) is a synthetic tetracycline that has been shown to have anti-cancer properties in vitro and in vivo, and inhibit angiogenesis - effects that may prove beneficial for several types of cancer. The aim of the present work was to study how Dox affects OS cell growth in vitro and in vivo and OS-driven pulmonary metastasis in vivo . Methods: In vitro, the effect of Dox was measured in MG-63 and 143B human OS cell viability, apoptosis, invasion and migration. In vivo, highly metastatic 143B cells were orthotopically implanted into the tibia of SCID mice. The tumour growth and pulmonary metastases between Dox treated and untreated, non-amputated and early amputated xenografts were examined. Results: In vitro, Dox decreased viability, inhibited invasion, migration, and induced the apoptosis of OS cells. In vivo, Dox significantly enhanced tumour necrosis at primary OS sites, similarly to its in vitro effect, and downregulated the expression of Ki67, MMP2, MMP9, VEGFA and ezrin. It also decreased circulating VEGFA and MMP9 protein levels, in line with the decreased metastatic burden in Dox-treated mice (non-amputated and early-amputated). Conclusions: Reprofiling of Dox can prevent the evolvement of pulmonary micro-metastases to clinically detectable macro-metastases and suppress the lethal progress of OS by inhibiting the expression of MMPs, VEGFA and ezrin at primary sites.